Comparative genomics yields insights into niche adaptation of plant vascular wilt pathogens. - Steven J Klosterman (Public Library of Science (PLoS), 2011)
The vascular wilt fungi Verticillium dahliae and V. albo-atrum infect over 200 plant species, causing billions of dollars in annual crop losses. The characteristic wilt symptoms are a result of colonization and proliferation of the pathogens in the xylem vessels, which undergo fluctuations in osmolarity. To gain insights into the mechanisms that confer the organisms' pathogenicity and enable them to proliferate in the unique ecological niche of the plant vascular system, we sequenced the genomes of V. dahliae and V. albo-atrum and compared them to each other, and to the genome of Fusarium oxysporum, another fungal wilt pathogen. Our analyses identified a set of proteins that are shared among all three wilt pathogens, and present in few other fungal species. One of these is a homolog of a bacterial glucosyltransferase that synthesizes virulence-related osmoregulated periplasmic glucans in bacteria. Pathogenicity tests of the corresponding V. dahliae glucosyltransferase gene deletion mutants indicate that the gene is required for full virulence in the Australian tobacco species Nicotiana benthamiana. Compared to other fungi, the two sequenced Verticillium genomes encode more pectin-degrading enzymes and other carbohydrate-active enzymes, suggesting an extraordinary capacity to degrade plant pectin barricades. The high level of synteny between the two Verticillium assemblies highlighted four flexible genomic islands in V. dahliae that are enriched for transposable elements, and contain duplicated genes and genes that are important in signaling/transcriptional regulation and iron/lipid metabolism. Coupled with an enhanced capacity to degrade plant materials, these genomic islands may contribute to the expanded genetic diversity and virulence of V. dahliae, the primary causal agent of Verticillium wilts. Significantly, our study reveals insights into the genetic mechanisms of niche adaptation of fungal wilt pathogens, advances our understanding of the evolution and development of their pathogenesis, and sheds light on potential avenues for the development of novel disease management strategies to combat destructive wilt diseases.